2006
DOI: 10.3748/wjg.v12.i17.2701
|View full text |Cite
|
Sign up to set email alerts
|

Functional dyspepsia: Are psychosocial factors of relevance

Abstract: The pathogenesis of Functional Dyspepsia (FD) remains unclear, appears diverse and is thus inadequately understood. Akin to other functional gastrointestinal disorders, research has demonstrated an association between this common diagnosis and psychosocial factors and psychiatric morbidity. Conceptualising the relevance of these factors within the syndrome of FD requires application of the biopsychosocial model of disease. Using this paradigm, dysregulation of the reciprocal communication between the brain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 72 publications
2
33
0
4
Order By: Relevance
“…Review studies such as that of Barry and Dinan also confirmed the co-morbidities of anxi-ety, depressive, somatoform disorders, and neuroticism in patients with functional dyspepsia. 19 These psychological problems are commonly seen in most digestive disorders so that in the study of Van Oudenhove et al, 46 anxiety, depression, and somatization were used as the most important variables on separating functional gastroduodenal disorders (FGD). The results of Faramarzi et al 20 in Iran revealed that psychological problems (depression and anxiety) were more prevalent in FD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Review studies such as that of Barry and Dinan also confirmed the co-morbidities of anxi-ety, depressive, somatoform disorders, and neuroticism in patients with functional dyspepsia. 19 These psychological problems are commonly seen in most digestive disorders so that in the study of Van Oudenhove et al, 46 anxiety, depression, and somatization were used as the most important variables on separating functional gastroduodenal disorders (FGD). The results of Faramarzi et al 20 in Iran revealed that psychological problems (depression and anxiety) were more prevalent in FD patients.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with other previous studies. [19][20][21][22]44 For example, Norton et al 45 showed that participants suffering from functional dyspepsia showed significant differences in terms of anxiety and depression when compared with controls. The results of Filipović et al 21 also approved these facts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Danish study poor socio-economic status emerged as an important risk factor for peptic ulcer disease which exerts its effect independently of H pylori infection [20] . In functional dyspepsia the role of psychosocial factors continues to be the subject of debate [21] . In this respect our findings support those previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…1%) addressed different psychological aspects of gastrointestinal diseases, such as quality of life [1] and psychological impact of chronic g astrointestinal diseases [2] , mental problems with hepatitis [3] , family occurrence [4] and other psychological aspects [5] of functional bowel disorders. Only 1 paper reported experimental data on brain imaging [6] and only one review paper addressed the psycho-physiological aspects of visceral pain [7] .…”
mentioning
confidence: 99%